The dragon round - Power, Stephen S. (Simon & Schuster, 2016)
"A swashbuckling adventure with a dark side for fans of George R.R. Martin and Naomi Novik--when a ship captain is stranded on a deserted island by his mutinous crew, he finds a baby dragon that just might be the key to his salvation"--